Investigation of an HIV transmission cluster centred in South Wales. Issue 5 (2nd July 2008) - Knapper, C M; Roderick, J; Smith, J; Temple, M; Birley, H D L
Abstract : Objective: To describe an HIV transmission cluster centred in South Wales by the analysis of partner notification outcomes and demographic characteristics of individuals identified in the sexual network. Methods: After diagnosis of the index case, HIV testing and partner notification were undertaken by Cardiff Genitourinary Medicine Clinic in collaboration with the local Health Protection Team, National Public Health Service for Wales and Terrence Higgins Trust Cymru. Rapid test and standard venepuncture methods were used for HIV screening and the resulting clinical and behavioural data were analysed. Results: Of the 123 individuals identified in the sexual network, all were men who had sex with men (MSM) except for seven men who self-identified as bisexual and five heterosexual women. Fifteen new cases of HIV were diagnosed; all were men. Partner notification outcomes are as follows: 104 provider referrals were made, 57 were successfully contacted with known outcomes, 14 were successfully contacted but with unknown outcomes and 33 were uncontactable. Fifteen patient referrals were made, 11 had known outcomes but four had unknown outcomes. Four patients self-referred. Eleven reported previous HIV diagnosis. The sexual network was distributed over South and West Wales extending into England, with high reported rates of unprotected anal intercourse, previous HIV tests and concurrent sexually transmitted infections. A one in four positive rate for those with a known HIV status outcome and a 68% provider referral success rate compares favourably with other studies. Conclusions: Partner notification revealed a relatively young, well-educated HIV network with high-risk behaviour and ongoing transmission despite previous knowledge and awareness of HIV. This analysis adds to the evidence supporting HIV partner notification in MSM.